2015
DOI: 10.1080/00224499.2014.1003773
|View full text |Cite
|
Sign up to set email alerts
|

How Much More XXX is Generation X Consuming? Evidence of Changing Attitudes and Behaviors Related to Pornography Since 1973

Abstract: We use data from the General Social Survey (GSS) over a 40-year period (1973-2012) to evaluate changes in attitudes about pornography and pornography consumption among American young adults. One of the major challenges in making comparisons across birth generations is separating the effect of birth cohort from age and period effects. We use an intrinsic estimator to separately identify the effects of age, birth cohort, and time period using 40 years of repeated cross-section data. We find that, relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(144 citation statements)
references
References 23 publications
8
133
1
2
Order By: Relevance
“…We consider gender first. Among the most consistent findings in pornography research is that men are far more likely to view pornography than women, and to do so more frequently (Carroll et al, 2008;Perry, 2016;Peterson & Hyde, 2011;Poulsen et al, 2013;Price et al, 2016;Regnerus et al, 2016;Wright, 2013;Wright et al, 2013). While some scholars suggest that evolutionary biology may play a role, other analyses have shown that much of this gender difference is due to internalized norms of "appropriate" sexual desire and behavior for men and women (Johansson & Hammaren, 2007;Peterson & Hyde, 2011).…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 97%
See 3 more Smart Citations
“…We consider gender first. Among the most consistent findings in pornography research is that men are far more likely to view pornography than women, and to do so more frequently (Carroll et al, 2008;Perry, 2016;Peterson & Hyde, 2011;Poulsen et al, 2013;Price et al, 2016;Regnerus et al, 2016;Wright, 2013;Wright et al, 2013). While some scholars suggest that evolutionary biology may play a role, other analyses have shown that much of this gender difference is due to internalized norms of "appropriate" sexual desire and behavior for men and women (Johansson & Hammaren, 2007;Peterson & Hyde, 2011).…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 97%
“…Despite these limitations, which we discuss in greater detail below, because the survey question has been consistent over this time period it allows us to track trends in pornography viewership across different groups of interest. This outcome has also been widely used in previous studies of pornography consumption over time (Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Price et al, 2016;Regnerus, Gordon, & Price, 2016;Wright, 2013;Wright et al, 2013), and thus, is profitably used here to address our research questions.…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 99%
See 2 more Smart Citations
“…While pornography use in general predicts lower marital quality later on regardless of whether the users are violating their own moral views, viewing pornography at higher frequencies while contradicting one's moral values may potentially take a toll on relationship quality. As attitudes toward pornography become more accepting in the United States (Lykke & Cohen, 2015;Price, Patterson, Regnerus, & Walley, 2016), it is possible that any moderating effect of moral incongruence will be attenuated. Conversely, if the attitudes of young Americans toward pornography are not changing tremendously (see Price et al, 2016) even as pornography use continues to increase, it may be that more Americans will find themselves in the situation where they are violating their own consciences in viewing pornography, thus holding greater consequences for mental health (Grubbs et al, 2015b;Perry, 2017b) or intimate relationships.…”
Section: Discussionmentioning
confidence: 99%